Analysis of the three fundamental frameworks of Hindu: Karya Agung Mamungkah Wrhespati Kalpa Utama Ngenteg Linggih at Pura Agung Mpu Kuturan Singaraja - Ketut Agus Nova; I Gusti Ngurah Sudiana; Ni Gusti Ayu Kartika (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: This study examines the implementation of the Karya Agung Mamungkah Wrhaspati Kalpa Utama Ngenteg Linggih at Pura Agung Mpu Kuturan, Institut Agama Hindu Negeri (IAHN) Mpu Kuturan Singaraja, through the analytical framework of the Three Basic Frameworks of Hinduism (Tattwa, Susila, and Acara). The research is motivated by the temple’s “floating” functional status, which does not fully conform to traditional classifications such as Kahyangan Jagat, Kawitan, or Swagina temples, yet accommodates a large-scale and complex ritual typically associated with universal-scale temples. Methods: Data were collected through observation, in-depth interviews with key informants including religious leaders, lecturers, students, and institutional authorities, as well as document analysis. The data were analyzed using an interactive model involving data reduction, data display, and conclusion drawing, guided by the analytical framework of Tattwa, Susila, and Acara and supported by relevant sociological and religious theories. Findings: The findings reveal that the implementation of the ceremony is grounded in a conceptual synthesis that positions the campus temple as a hybrid form integrating elements of Kahyangan Jagat and Swagina. The ritual procession, guided by sacred texts such as Lontar Bhama Kertih, includes preparatory stages, core rituals such as Mecaru, Melaspas, and Melasti, culminating in Ngenteg Linggih as the installation of divine presence, and concluding with Masineb. This ritual has a multifaceted impact: it strengthens spirituality through experiential learning, fosters social solidarity (ngayah), enhances institutional quality and student engagement, and preserves cultural continuity across generations. Conclusion: The study concludes that the Karya Agung functions not merely as a ritual activity but as a transformative mechanism that integrates spirituality, institutional development, and cultural preservation within the context of higher education. Novelty/Originality of this article: This study introduces the concept of the campus temple as a “spiritual laboratory,” offering an innovative integrative model of Tattwa–Susila–Acara within modern higher education institutions.